The anti-tumor effects of evodiamine on oral squamous cell carcinoma (OSCC) through regulating advanced glycation end products (AGE) / receptor for advanced glycation end products (RAGE) pathway. Issue 1 (1st January 2021) - Ren, Liuyang; Lou, Ying; Sun, Mingyu
ABSTRACT: Evodiamine (EVO) is emerging as a novel anti-tumor drug, which is involved in the inhibition of cell proliferation and apoptosis. High-Mobility Group Box 1 (HMGB1)/RAGE is involved in invasive behavior of OSCC cells and angiogenesis. In this study, we evaluated the potential of EVO in OSCC in vitro and in vivo . We found that RAGE silencing suppressed HSC-4 cell proliferation and invasion, and tube formation of HUVEC. EVO showed marked inhibitory effects on the malignant behaviors of HSC-4 cells in a dose-dependent manner. Further experiments revealed that the RAGE overexpression was able to markedly block the effects of EVO on cell proliferation and invasion, and tube formation. By analyzing the expression of High-Mobility Group Box 1 (HMGB1) and RAGE in HSC-4 cells, the result showed that EVO slightly reduced HMBG1 levels and dramatically decreased RAGE levels, while RAGE overexpression did have no marked influences on HMBG1 levels. The anti-tumor effects of EVO were further confirmed in mouse oral squamous cell carcinoma xenograft models. Remarkable anti-tumor effects of EVO were also demonstrated, as presented by reduced tumor size and levels of HMBG1 and RAGE in tumor tissue of mouse oral squamous cell carcinoma xenograft models. The results demonstrated that EVO has a direct binding effect on HMGB1, but it may be involved in degrading the protein. More importantly, it can reduce the activity of RAGE pathway by affecting the binding between HMBG1 and RAGE. To conclude, EVO inhibited proliferation, invasion and angiogenesis of OSCC through affecting the downstream signal transduction system of AGE/RAGE by targeting RAGE.